Physicochemical Quality of Spent Broiler Breeder Hen Chicken Koftas Added with Different Levels of Raw Banana Dried Powder - Sharada, M V Sneha; Indumathi, J; Reddy, G V Bhaskar; Shakila, S; Mouli, A Chandra (Journal of Meat Science, 2023)
The present study was undertaken to evaluate the effect of different levels of raw banana dried powder on the quality characteristics of chicken koftas. The raw banana dried powder was incorporated at three different levels viz. 2, 4 and 6% in the formulation. The products were analyzed for various physicochemical and sensory attributes. pH, emulsion stability, cooking yield, water holding capacity, moisture, crude fibre and total ash content of the products showed significant (P<0.05) increasing trend with increase in levels of incorporation of raw banana dried powder. However, a significant (P<0.05) decrease in the crude protein and ether extract content of the chicken koftas was observed with increasing levels of incorporation. Sensory evaluation revealed that koftas prepared with 4 percent raw banana dried powder had superior scores (P<0.05) compared to 2 and 6 percent. Hence incorporation of raw banana dried powder at 4 percent level in chicken koftas was considered to be optimum.